Emerging synergistic strategies for enhanced antibacterial sonodynamic therapy: Advances and prospects - Hengyu Liu; Zhezhu Nan; Chen Zhao; Liang Bai; Linrong Shi; Chenhui He; Daocheng Wu; Mingxi Wan; Yi Feng (Ultrasonics Sonochemistry)
Antibacterial therapy has been extensively applied in medical field to alleviate the severity and mortality of infection. However, it still exists some issues such as drug side effects, limited efficacy and bacterial resistance. Among the alternative therapies, antibacterial sonodynamic therapy (aSDT) has been explored as a promising approach to tackle those crises. It is meaningful to investigate superior strategy to augment the therapeutic efficacy of aSDT. This review summarizes the potential aSDT-based antibacterial mechanisms and comprehensively discusses the prevailing synergistic strategies, such as nanomaterials-based aSDT antibacterial strategy, aSDT + strategy with physical, chemical and biological methods. Moreover, we also reviewed the medical applications of aSDT strategies. Finally, the perspectives on the current challenges that need be resolved in aSDT are proposed. We expect that this review could provide robust support to expedite the clinical applications of aSDT.